Public Service Delivery and the Livelihood Adaptive Capacity of Farmers and Herders: The Mediating Effect of Livelihood Capital - Fanglei Zhong; Caoji Ying; Di Fan (Land, 2022)
Improving the provision and equitable accessibility of public services is an important aspect of poverty alleviation and necessary for rural revitalization. Farmers’ livelihood adaptive capacity is an important foundation for rural revitalization, and the mechanism by which it is influenced by public service delivery requires clarification. In this study, we construct a theoretical framework of public service delivery–livelihood capital–livelihood adaptive capacitiy of farmers and herders to measure the level and quality of public service delivery, based on the level of satisfaction of 334 farmers and herders we surveyed. The relationship between the three elements was verified using mediated effects analysis, which helped to accurately identify the key shortcomings of public service delivery and improve the delivery of public services to enhance the sustainable livelihood adaptive capacity of farmers and herders. We found that public service delivery has a significant positive impact on the livelihood adaptive capacity of farmers and herders, while livelihood capital plays an important mediating role, enhancing the direct impact of public service delivery. Thus, the government should pay attention to this transfer mechanism and actively cultivate farmers’ and herders’ livelihood capital to optimize the effects of rural public service delivery.